Baseball team, 1870 - Munro, Melville S.; Rollins, Edwin B. (Tufts Archival Research Center, 2005)
5x7; Melville S. Munro Collection - MS036/008-0023#004-pg. 37 and 3x5 copy negative credited to Rollins